BIMBINGAN PENGEMBANGAN WAWASAN KARIR BAGI PESERTA DIDIK KELAS III DI SD NEGERI WELAI - Silas Maniata; Salomi Duka, Yosin E. Djolelang, Vebrianus Petrus Barai, Yessy Mata, Petrus Mau Tellu Dony, Halena M (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to determine the implementation of thematic learning in career supervision for children with special needs at Welai Elementary School, including various career challenges and efforts to resolve them. The method used in this study was descriptive qualitative. The subject of this study was Mrs. Eni Nengsi Maata, S.Pd., a third-grade teacher at Welai Elementary School. She is a teacher with a career and talents and applies her career guidance to her students. Data collection techniques used interviews and documentation. This study describes the implementation of thematic learning, in which teachers provide specific guidance using easily understood body language and clear lip movements when communicating, developing students' interests and talents, and using methods, P5 learning, and infrastructure tailored to students' needs. Challenges in the implementation of career learning include teachers' limited knowledge of students' careers or local interests, difficulties in developing their potential, and limitations in media and infrastructure. Efforts by teachers and the school in career development.